The Influence of Ibn Sahnun's Th Pengaruh Pemikiran Ibnu Sahnun Dalam Merealisasikan Pendidikan Karakter - Ilham Romadona; Muhammad Haikal Saputra; Muhammad Abdul Aziz Al-Maghribi; Wan Muhammad Fariq (Fakultas Tarbiyah dan Ilmu Keguruan UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
This study aims to explore Ibn Sahnun's thoughts on the role of teachers in character education, especially those contained in his work Adab Al-Muallimin, and examine its relationship to character education in the modern era. We conducted this study using Literature Study, namely by observing and researching existing scientific works, such as journals, books and relevant articles. From the various data we collected, it can be explained that Ibn Sahnun emphasized the importance of teacher role models, a humanist approach, and instilling moral values ​​in the learning process. Teachers, according to Ibn Sahnun, do not only act as educators, teachers are role models, as moral guides, and facilitate the learning process to be more conducive. Ibn Sahnun's thoughts on character education are still relevant today, especially in facing the challenges of globalization and moral crisis. This study is expected to contribute to the development of holistic and meaningful moral education strategies for the next generation of the nation.